Neuroprotection in the Treatment of Glaucoma - Astrianda Nadya Suryono (PT Dexa Medica, 2023)
Glaucoma is a neurodegenerative disease with certain characteristics of progressive damage to the optic nerve, loss of retinal ganglion cells (RGC) and their axons, accompanied by typical visual defect. Increased intraocular pressure (IOP) is the main risk factor for glaucoma. Some study stated that RGC death is still progressing despite the use of IOP-lowering medications. The main aim of glaucoma treatment remains to lower IOP, however neuroprotective agents have increased interests due to its effects to prevent or slow down the rate of RGC death other than IOP-dependent mechanisms. Production of glutamate and nitric oxide is known as one of the contributing factors of RGC death, and neuroprotective agents that work by targeting the production of glutamate and nitric oxide can be a valuable option to prevent further RGC death.